Sugar-sweetened beverage intake and serum testosterone levels in adult males 20–39 years old in the United States - Liang Chen; Yu-Mei Xie; Jian-Hao Pei; Jian Kuang; Hong-Mei Chen; Zhong Chen; Zhong-Wen Li; Xiao-Ying Fu; Long Wang; Shui-Qing Lai; Shu-Ting Zhang; Zhi-Jiang Chen; et al. (Reproductive Biology and Endocrinology, 2018)
Abstract Background This population-based study was designed to investigate whether consumption of sugar-sweetened beverages (SSB) is associated with lower serum total testosterone concentration in men 20–39 years old. Methods All data for this study were retrieved from the National Health and Nutrition Examination Survey (NHANES) 2011–2012. The primary outcome was serum testosterone concentration, and main independent variable was SSB intake. Other variables included age, race/ethnicity, poverty/income ratio, body mass index (BMI), serum cotinine, heavy drinking, and physical activity. Results Among all subjects (N = 545), 486 (90.4%) had normal testosterone levels (defined as ≥231 ng/dL) and 59 (9.6%) had low testosterone levels (defined as < 231 ng/dL). Multivariate logistic regression revealed the odds of low testosterone was significantly greater with increasing SSB consumption (Q4 [≥442 kcal/day] vs. Q1 [≤137 kcal/day]), adjusted odds ratio [aOR] = 2.29, p = 0.041]. After adjusting for possible confounding variables, BMI was an independent risk factor for low testosterone level; subjects with BMI ≥ 25 kg/m2 had a higher risk of having a low testosterone level than those with BMI < 25 kg/m2 (aOR = 3.68, p = 0.044). Conclusion SSB consumption is significantly associated with low serum testosterone in men 20–39 years old in the United States.